Spatial competition and equilibrium in a circular market - Andreas Kopp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
The paper presents an analysis of spatial competition between two firms in a circular market. It is shown that the existence problem of a Bertrand-Nash- Equilibrium exists for the circular market in the same way as for the linear and bounded market. This is demonstrated by directly studying the reaction functions of the competing producers and without referring to merely technical fixed point arguments. The existence problem is solved by adding a move structure to the game, regarding market entry as sequential and taking place in historical time.
Keywords: 330; Räumlicher Wettbewerb; Theorie